Pesantren Entrepreneur dan Analisis Kurikulum Pesantren Mukmin Mandiri Waru Sidoarjo dalam Pengembangan Dunia Usaha - Anam, Saeful (Koordinatorat Perguruan Tinggi Agama Islam Swasta Wilayah IV Surabaya, 2016)
This article explores a new model of Islamic boarding schools in the modern era. Various innovations appear to be made as an urgent change to Indonesiaâs educational system. âPesantren entrepreneurâ is, among other, a new way (manhaj) of Indonesiaâs contemporary education to reduce unemployment and overcome poverty. The concept is that students (santri) are not merely taught such religious lesson (tafaqquh fÃ® al-dÃ®n) but they also trained to be able to understand and possess ability within economics aspect (tafaqquh fÃ® al-tijÃ¢rah). It is assumed that the more pesantren entrepreneur are established the stronger the nationâs economy will be. It has been undeniable fact that Indonesiaâs independent and its development have been strongly supported by Islamic educational system, namely Islamic boarding schools (pesantren) which widely spread across Nusantara. The implementation of pesantren entrepreneur has been initiated from a strong desire to develop pesantren through active, creative, productive and innovative actions which will subsequently provide pesantren chance to independently maintain its existence. The author argues that such an effort will be able to create better future for our next generation.